Genealogy of the South Indian deities : an English translation of Bartholomäus Ziegenbalg's original German manuscript with a textual analysis and glossary - Ziegenbalg, Bartholomaeus, 1683-1719 (RoutledgeCurzon studies in Asian religion., 2005)
For the first time, the work Genealogy of the South Indian Deities of the first Protestant missionary to India, Bartholomaeus Ziegenbalg (1682-1719), is made accessible to an English readership.